Promoting Responsible Tourism Practices - Dr.Usha Mishra; Tripti Dixit (AG Volumes, 2026)
By responsible tourism we mean that kind of eco-friendly tourism which chiefly focuses minimizing its negative effects on environment, culture and localities of that particular place while enhancing the contribution which has to be positive for the host communities, environment as well as culture. Responsible tourism promotes sustainable and ethical travel practices and mainly focuses not only on preserving heritage but also encouraging responsible travel behavior. Changes in traveller’s behavior are among the most significant issues in the current revolution of the tourism industry. The transition to responsible tourism is primarilydriven by tourism destination related elements and the strengthof the impact related to maintain the quality of life of the local people, redistributing the benefits of tourism for travel destination as well as expanding thevalueanddistinctivenessof the travel destination product and maintaining long term attractiveness within the capacity of travel destination and efficient use of its tourism resources.In the words of Cap Town declaration “Responsible tourism is about making better places for people to live in and better places for people to visit. It is important to find out how visitors from different part of the world support the principles of responsible tourism in the expression of their behavior. This paper will explore on key principles challenges and provide recommendation for implementation